Assessment of the functional outcome in patients with olecranon fracture treated by tension band wiring technique - Dhakal, Rabi Mohan; Bista, Krishna Bahadur; KC, Suman; Parajuli, Anjali (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Tension Band Wiring (TBW) is a common fixation method for olecranon fractures. This study aims to evaluate the functional outcomes of patients treated with TBW, using the Mayo Elbow Performance Score (MEPS).Methods: Thirty patients with olecranon fractures were randomly selected for operative treatment, meeting the inclusion criteria. They were followed up for six months, with outcomes assessed using the Visual Analogue Scale (VAS) and MEPS at the final follow-up.Results: Among the 30 patients evaluated, males comprised 70%, and 30% were females. The olecranon of the right side was more commonly injured (56.67%). The mean age of participants was 34.10 years (range 18-64 years). Most fractures resulted from fall injuries (46.67%), followed by Road Traffic Accidents (43.33%). The most frequent fracture type was Mayo Type 2 (56.67%), followed by Type 3 (43.33%). The mean time from injury to surgery was 3.93 days, and the average union time was 7.57 weeks. At three months, the mean VAS score was 1.20, improving to 0.63 at six months. The mean MEPS at three months was 84.83, increasing to 92.33 at six months. At the final follow-up, 20 patients had excellent outcomes, 8 had good outcomes, and two had fair outcomes.Conclusions: Open reduction and internal fixation with TBW leads to excellent functional outcomes, supporting its continued use as the gold-standard technique based on solid biomechanical principles.